Effects of Dry- and Wet-ageing on Flavor Compounds and Eating Quality of Low Fat Hanwoo Beef Muscles - Ha, Yoonkyung; Hwang, Inho; Ba, Hoa Van; Ryu, Sangdon; Kim, Younghoon; Kang, Sun Moon; Kim, Jinhyoung; Kim, Yunseok; Cho, Soohyun (Food science of animal resources, 2019)
The present study aimed at investigating the effects of dry- and wet-aging methods on flavor compounds and sensory properties of low fat Hanwoo beef muscles. All the beef samples were obtained from 2-grade carcasses of Hanwoo cows. The beef samples used in the dry- and wet-aging methods were prepared in the forms of quarter beef (bone-in) and cuts (boneless), respectively. The dry-aging was carried out at 2°C-4°C and humidity of 65%-85%, while the wet-aging was done at 1°C for 0, 20, 40, and 60 d. At each aging time, three muscles: (LT), (GM) and (SM) were taken from the corresponding quarters and cuts, and used for the flavor compounds and sensory analyses. Results showed that both aging methods significantly increased the concentrations of flavor compounds and total amount of all classes of the flavor compounds as the aging time increased (p<0.05). In the dry-aging method, the GM and SM muscles presented significantly higher total amounts of pyrazines and sulfur-containing compounds compared to the LT muscle (p<0.05). Both the aging methods improved the eating quality attributes, indicating by increased scores of sensorial attributes with increased aging time for all the muscles studied (p<0.05). However, compared to the wet-aging, the dry-aging method resulted in significantly higher scores of tenderness and flavor for the GM and SM muscles after 40 to 60 d. Thus, postmortem aging, especially the dry-aging method could be used to improve eating quality attributes (tenderness and flavor) of low fat beef muscles such as GM and SM.